Introduction à la gestion de projet (Assemble You, 2022)
Welcome to Assemble You Audio Learning. Few industries can't benefit in some way from project management. Whether it's building a skyscraper, developing new software, installing a plumbing system, designing a real estate project, organizing a a business convention or even planning a birthday party, project management is essential to the success of each of these initiatives. The Investopedia team aptly proposes to define this term as follows: Project management involves planning and organizing a company's resources to complete a specific task, event, or mission. . It can be a one-time project or an ongoing activity, and the resources to be managed typically include personnel, finance, technology, and/or intellectual property. Regardless of the project in question, the majority of the resources listed above will be involved in the project in some way and will need to be properly organized to ensure that it runs smoothly. Learning Objectives Discover how project management can be applied in almost any industry Learn what project management really entails Glimpse some popular project management methodologies.